2014
DOI: 10.1080/00423114.2014.944870
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of vehicle–turnout interaction by optimising the shape of crossing nose

Abstract: Proper rail geometry in the crossing part is essential for reducing damage on the nose rail. To improve the dynamic behaviour of turnout crossings, a numerical optimisation approach to minimise rolling contact fatigue (RCF) damage and wear in the crossing panel by varying the nose rail shape is presented in the paper. The rail geometry is parameterised by defining several control cross-sections along the crossing. The dynamic vehicle-turnout interaction as a function of crossing geometry is analysed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 14 publications
0
62
0
2
Order By: Relevance
“…In [3], it was observed from the field measurements that after grinding/welding maintenance of the crossing, not only was the magnitude of impact significantly reduced but also the location of impact was shifted -leading to wider spread of impacts on the nose rail. A close look at the geometric effect on the transition location has been documented in [12], in which it is shown that both the nose rail shape and the vertical distance between the top of the wing rail and the nose rail have considerable influence on the impact location.…”
Section: Criteria Of Wheel Transition Improvementmentioning
confidence: 99%
See 3 more Smart Citations
“…In [3], it was observed from the field measurements that after grinding/welding maintenance of the crossing, not only was the magnitude of impact significantly reduced but also the location of impact was shifted -leading to wider spread of impacts on the nose rail. A close look at the geometric effect on the transition location has been documented in [12], in which it is shown that both the nose rail shape and the vertical distance between the top of the wing rail and the nose rail have considerable influence on the impact location.…”
Section: Criteria Of Wheel Transition Improvementmentioning
confidence: 99%
“…The studied turnout is a standard one (right turn) with a curve radius of 725 m and a crossing angle of 1:15, which is the same model as in [3,12]. In the present paper, the investigations are only for a vehicle passing in the main-facing direction.…”
Section: Basic Vehicle-turnout Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they also evaluated the structural design of turnout switches based on this method. Markine, Wan and Wang et al [6][7][8] optimized the track stiffness and rail profiles in order to reduce the dynamic wheel-rail interaction at turnout zones and solve problems such as rail wear and fatigue of turnout rails. Pletz et al [9] presented a finite element model for crossing with a single running wheel according to the wheel-rail vibration, elastic wheel deformation and plastoelastic rail deformation, in order to calculate the dynamic wheel-rail interaction, then they also presented a simplified finite element model for calculating the dynamic wheel-crossing interaction [10], according to the influence of grid precision and calculation time, through setting appropriate grid sizes.…”
Section: Introductionmentioning
confidence: 99%